2015
DOI: 10.1063/1.4918591
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductance of superlattice junctions

Abstract: We use molecular dynamics simulations and the lattice-based scattering boundary method to compute the thermal conductance of finite-length Lennard-Jones superlattice junctions confined by bulk crystalline leads. The superlattice junction thermal conductance depends on the properties of the leads. For junctions with a superlattice period of four atomic monolayers at temperatures between 5 and 20 K, those with mass-mismatched leads have a greater thermal conductance than those with mass-matched leads. We attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…This is consistent with the findings in Ref. 46, where it is demonstrated that the thermal circuit model underpredicts the thermal conductance of LJ-based crystalline SL junctions that are confined between two leads.…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with the findings in Ref. 46, where it is demonstrated that the thermal circuit model underpredicts the thermal conductance of LJ-based crystalline SL junctions that are confined between two leads.…”
Section: Resultssupporting
confidence: 93%
“…This artificially modified mass method has been widely used to study interfacial thermal resistance. [ 74–76 ]…”
Section: Resultsmentioning
confidence: 99%
“…This artificially modified mass method has been widely used to study interfacial thermal resistance. [74][75][76] The temperature profile of the regular-"heavy" mass-mismatched heterostructure is shown in Figure 3. Importantly, it is worth noting that there is pronounced temperature jump across the interface, which are 19.59 K (positive thermal bias) and 19.94 K (negative thermal bias) for armchair mass-mismatched heterostructure, and 20.96 K (positive thermal bias), 20.62 K (negative thermal bias) for zigzag BP mass-mismatched heterostructure, respectively.…”
Section: Comparative Study With the Mass-mismatched Bp Junctionmentioning
confidence: 99%
“…Therefore, it is interesting to asses to what extent subsequent DWs behave like independent scattering centers with resistances that barely sum up, a sound assumption in a purely diffusive transport regime. 31 For this reason, we next study the thermal conduction in systems with two DWs. In particular, we consider two cases of DW pairs: in one case the spacing between them is 1.5 nm, in the other 4 nm.…”
mentioning
confidence: 99%